1993
DOI: 10.1016/0014-5793(93)80152-k
|View full text |Cite
|
Sign up to set email alerts
|

The KH domain occurs in a diverse set of RNA‐binding proteins that include the antiterminator NusA and is probably involved in binding to nucleic acid

Abstract: New findings are presented for the ~ 50 residue KH motif, a domain recently discovered in RNA‐binding proteins. The conserved sequence is ~ 10 residues larger than previously reported. Profile searches have revealed new members of this family, including two, E. coli NusA and human GAP‐associated p62 phosphoprotein, for which RNA‐binding data exists. A nus A homolog was detected in the RNA polymerase gene complex of six archaebacterial species and may encode an antiterminator. All KH‐containing proteins are lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(155 citation statements)
references
References 39 publications
3
150
0
2
Order By: Relevance
“…If it is truncated by five amino acids at either end, the binding is reduced (It0 et al, 1994;this paper). Most previous descriptions of KH domains (Dreyfuss et al, 1993;Siomi et al, 1993a;Gibson et al, 1993;Buckanovich et al, 1993;Siomi et al, 1994Siomi et al, , 1995Duncan et al, 1994) have only included the N-terminal part, ending shortly after the middle variable region, and this is clearly insufficient for nucleic Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If it is truncated by five amino acids at either end, the binding is reduced (It0 et al, 1994;this paper). Most previous descriptions of KH domains (Dreyfuss et al, 1993;Siomi et al, 1993a;Gibson et al, 1993;Buckanovich et al, 1993;Siomi et al, 1994Siomi et al, , 1995Duncan et al, 1994) have only included the N-terminal part, ending shortly after the middle variable region, and this is clearly insufficient for nucleic Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel motif was detected in heterogenous nuclear ribonucleoprotein K (hnRNP-K) (Matunis et al, 1992; and one or more were soon discovered in a number of other putative nucleic acid binding proteins from both eukaryotes, eubacteria and archaea (Gibson et al, 1993;Siomi et al, 1993a;. These include the fragile-X protein (FMR1) (Verkerk et al, 1991;Siomi et al, 1993b), the Ri auto antigen (nova) (Buckanovich et al, 1993), a putative transcription activator FBP (Duncan et al, 1994), the poly(rC)-binding proteins (PCBP) 1 and 2 (Leffers et al, 1995) and HBP (McKnight et al, 1992) from human, the yeast merl (Engebrecht and Roeder, 1990) and HX proteins (Delahodde et al, 1986), ribosomal proteins from different species (Kao et al, 1990;Klenk et al, 1991) and the bacterial nusA (see Musco et al, 1996, for latest review).…”
Section: Hagen Denmarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Sam68 is a nuclear protein that consists of at least six proline rich regions, an RNA binding region referred to as the hnRNP K homology (KH) domain (Gibson et al, 1993;Siomi et al, 1993) and a tyrosinerich C-terminal region (Wong et al, 1992;Fumagalli et al, 1994;Chen et al, 1997;Ishidate et al, 1997). Sam68 binds to poly(U) homopolymeric ribonucleotides, in vitro (Taylor and Shalloway, 1994;, and its ability to bind ribonucleotides can be negatively regulated by tyrosine phosphorylation, as well as by interactions with the Src SH3 domain (Taylor et al, 1995;Wang et al, 1995).…”
Section: Nuclear and Perinuclear Targets Of Srcmentioning
confidence: 99%
“…Several laboratories showed that a subfamily of hnRNPs, hnRNP K and hnRNP E1/E2, functions in translational regulation and/or mRNA stabilization in haematopoiesis. These proteins all bear three copies of an RNA binding motif, the hnRNP K homology (KH)-domain (Siomi et al, 1993, Gibson et al, 1993 consisting of 65-70 amino acids (Dejgaard andLeffers, 1996, Musco et al, 1996). In contrast to hnRNP E1/E2, hnRNP K carries additional domains: An N-terminal bipartite nuclearlocalization signal (NLS) and an hnRNP K-specific nuclear shuttling signal located between the second and third KHdomain, which confers the capacity for bi-directional transport across the nuclear envelope (Matunis et al, 1992, Michael et al, 1995.…”
Section: Introductionmentioning
confidence: 99%